2010
DOI: 10.1038/jcbfm.2010.186
|View full text |Cite
|
Sign up to set email alerts
|

External Globus Pallidus Stimulation Modulates Brain Connectivity in Huntington's Disease

Abstract: Positron emission tomography with O-15-labeled water was used to study at rest the neurophysiological effects of bilateral external globus pallidus (GPe) deep brain stimulation in patients with Huntington's disease (HD). Five patients were compared with a control group in the on and off states of the stimulator. External globus pallidus stimulation decreased neuronal activity and modulated cerebral connectivity within the basal ganglia-thalamocortical circuitry, the sensorimotor, and the default-mode networks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 16 publications
3
35
0
1
Order By: Relevance
“…15 A further PET study showed that altered excitation of the striatum can modulate widespread cortical networks. 62 While such disconnection of the posterior putamen from functionally specific cortical networks can result in compensatory increases in other striatal connections, such as that observed in patients with Parkinson disease, 13 we observed no compensatory increased striatal synchrony in symp-HD individuals.…”
Section: Discussionmentioning
confidence: 51%
“…15 A further PET study showed that altered excitation of the striatum can modulate widespread cortical networks. 62 While such disconnection of the posterior putamen from functionally specific cortical networks can result in compensatory increases in other striatal connections, such as that observed in patients with Parkinson disease, 13 we observed no compensatory increased striatal synchrony in symp-HD individuals.…”
Section: Discussionmentioning
confidence: 51%
“…Interestingly, previous studies have reported connectivity between these two regions with effective connectivity measures (Marchand et al, 2007). PET studies involving deep brain stimulation of the globus pallidus in Huntington Disease have reported decreased regional CBF in the precuneus (Ligot et al, 2011). Precuneus is considered to be part of the self-referential network, the alterations of which have been previously explored in the realm of task-based fMRI in SAD, particularly for the evaluation of mindfulness-based intervention programs in unmedicated patients (Goldin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Ligot et al [10] performed GPe DBS in five patients with genetically confirmed HD. This study used positron emission tomography imaging to assess how DBS altered neuronal activity in the basal ganglia-thalamocortical circuitry and motor network.…”
Section: Gpementioning
confidence: 99%
“…Due to the GPe being more affected, there is a preferential involvement of the indirect pathway of the basal ganglia-thalamocortical circuitry. This reduced inhibition of the GPe leads to excessive inhibition of the subthalamic nucleus (STN) and hyperstimulation of the motor cortex downstream [10]. Chorea is the end result of this hyperstimulation.…”
Section: Pathophysiology Of Hdmentioning
confidence: 99%
See 1 more Smart Citation